Zasady opracowania podstawowego modelu dyscypliny [naukowej] w systemie dydaktycznym szkolnictwa wyższego na Ukrainie - Losyeva, Nataliya; Strelnikov, Viktor (Wydawnictwo Collegium Verum (wcześniej: Szkoła Wyższa Przymierza Rodzin), Warszawa 2020, 2020)
on the competence–based approach. The didactic system planning is performed in accordance with the educational standards, their consecutive goals, contents and the program–based tuition results. The article reveals the theoretical basics of the content–based modules of the subject within the didactic system of the professional competences formation for the future specialists, namely it touches upon the principles of goal— orientation, social importance, scientific approach to the training materials; practical approach; combination of complex, integral and didactical goals of the subject; the completeness of the module training materials; relevant self–sufficiency of the module elements; the realisation of the feedback; the appropriate application of the training and methological materials; the integration of the educational materials within the module; generalisation, interconnection and logical attitude to the training. The article investigates the essence of each of the given principles.
ПРИНЦИПЫ ПРОЕКТИРОВАНИЯ СОДЕРЖАТЕЛЬНЫХ МОДУЛЕЙ ДИСЦИПЛИНЫ В ДИДАКТИЧЕСКОЙ СИСТЕМЕ ВЫСШЕГО ОБРАЗОВАНИИ УКРАИНЫ
Keywords: didactic system; principles of education; content–based module of the subject; credit–based modular learning; competence approach; project–based learning; planning